The Speech Act of Basuki Tjahja Purnamas’ Utterences on His Visit to Kepulauan Seribu Regency - Wijaya, Dendi (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2019)
This research is a descriptive study, looking at the speech act model in the remarks of Basuki Tjahja Purnama (BTP) in the face of the Kepulauan Seribu Regency. The benefits of this research can contribute to the analysis of the development of pragmatic studies and provide knowledge and lessons for the community of social media users to be wiser in responding to every news. The data of this research contained BTP's speech in his speech in the Kepulauan Seribu which was analyzed using the theory, namely pragmatic theory. This research method is a descriptive research method. The data source used is a secondary data source. From this BTP speech several types of speech acts were found, namely representative / assertive, commissive, directive, and expressive speech acts. The results of data analysis showed that the dominant speech act used was assertive speech act which contained speech acts stated, speculated, claimed, acknowledged, and believed. Also found directive speech acts that contain speech acts calling, asking, and hoping. Furthermore, expressive speech acts given speech acts are satisfied, appreciated, and gratitude. While commissive speech acts only found speech acts in the form of promises and threats. However, if seen from the dominance of the speech, then the commissive speech act taken as a promise is the type of speech act that is most commonly found in BTP speeches in the Kepulauan Seribu.